Nutrient, Phytochemical Composition and Consumption Pattern of Soursop (Annona muricata) Pulp and Drink among Workers in University of Nigeria, Nsukka Community - Onyechi; Uchenna, Agatha; Ibeanu; Nkiruka, Vivienne; Eme; Eze, Paul; Kelechi; Madubike (Pakistan Journal of Nutrition, 2015)
Micronutrient malnutrition is a public health problem. This study evaluated the nutrient, phytochemical composition and consumption pattern of soursop (Annona muricata) pulp and drink. The soursop fruits were purchased from local market and a farm in Enugu State, Nigeria. The mature fruits were ripened for five days at room temperature. The ripen soursop fruits were peeled, the pulp handpicked, blended with 400mls of water to make the soursop drink. The soursop drink was then flavoured with four teaspoons of sugar syrup. The proximate composition, vitamin, mineral and phytochemical contents of the samples were determined using standard methods. The carbohydrate content of soursop pulp and drink was 72.71 and 83.47% respectively. The fibre content was 6.26 and 3.47%; retinol 192.50IU and 63.76IU; ascorbic acid was 22.59mg/100g and 34.71mg/100g for the pulp and drink respectively. The pulp and drink also contained a good amount of anthocyanin 6.44 and 7.35 mg/100g; flavonoids 9.32 and 5.24mg/100g and tannin 65.98 and 53.96mg/100g, respectively. It was concluded that soursop pulp and drink contained appreciable amount of micronutrients and can be incorporated into the diets for the vulnerable groups to improve their nutritional status.